Effect of Health Promotion on Knowledge and Practice of Health Protocols on Nursing Students in Lebak District - Sarma Eko Natalia Sinaga (STIKep PPNI Jawa Barat, 2023)
Aims: The impact of COVID-19 on human life is enormous, not only claiming many lives but also being able to cause setbacks in every aspect of life. Prevention of transmission of COVID-19 can be done by providing education about COVID-19 which can increase knowledge and awareness in implementing health protocols. This study will examine differences in knowledge and practice of health protocols before and after COVID-19 prevention interventions for nursing students in Lebak District. Methods: Quantitative research with the pre-experimental method, sampling technique with total sampling, and a sample of 166 nursing students. 2-stage data collection with a questionnaire via Google Forms. The research analysis is Pair T.Test. Intervention is carried out in 2 sessions in 1 week by providing education about COVID-19 to students and conducting simulations of keeping their distance, washing hands with soap, and removing masks. Results: The results showed an increase in the average value of knowledge before and after the intervention, from 9.14 to 9.62. Moreover, there is a significant difference in knowledge about COVID-19 after the intervention of 0.02. Meanwhile, in the practice of health protocols, there was also an increase in the average value from 28.19 to 28.60. Conclusion: After the intervention, there was no relationship between the practice of health protocols for nursing students; this was because the behaviour of COVID-19 practice protocol had not yet become a lifestyle for nursing students. For this reason, it is recommended to provide education and simulation of health protocols to get the expected behaviour.